PENINGKATAN KAPASITAS KELOMPOK USAHA DI PULAU SUMBA - Firmike Lidyatami Radja (LPPM Institut Pendidikan Nusantara Global, 2025)
The capacity-building program for economic institutions and community business groups in four districts on Sumba Island aims to strengthen business management by improving skills in enterprise financial management and in developing strategies for building long-term relationships with customers. This activity is part of the One Village One Product (OVOP) Program organized by the Provincial Office of Community and Village Empowerment (DPMD) of East Nusa Tenggara (NTT), in collaboration with higher education institutions on Sumba Island. The implementation method uses an educational and participatory approach. The results of the program show an improvement in participants’ understanding of financial record-keeping, separating personal and business finances, and preparing simple financial statements. In addition, participants also gained an understanding of the importance of customer orientation through enhanced service quality and continuous communication.